2006
DOI: 10.1302/0301-620x.88b6.17515
|View full text |Cite
|
Sign up to set email alerts
|

An alternative method for the treatment of nonunion of the tibia with bone loss

Abstract: In this retrospective study we evaluated the method of acute shortening and distraction osteogenesis for the treatment of tibial nonunion with bone loss in 17 patients with a mean age of 36 years (10 to 58). The mean bone loss was 5.6 cm (3 to 10). In infected cases, we performed the treatment in two stages. The mean follow-up time was 43.5 months (24 to 96). The mean time in external fixation was 8.0 months (4 to 13) and the mean external fixator index was 1.4 months/cm (1.1 to 1.8). There was no recurrence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 30 publications
2
33
1
5
Order By: Relevance
“…13 In our study we noted bone lengthening index i.e. duration required for formation of 1 cm of new bone was 1.48.…”
Section: Discussionsupporting
confidence: 50%
“…13 In our study we noted bone lengthening index i.e. duration required for formation of 1 cm of new bone was 1.48.…”
Section: Discussionsupporting
confidence: 50%
“…Such surgery may require a microvascular team and increase hospitalization time, cost, and morbidity. 7 We believe that if …”
Section: Discussionmentioning
confidence: 99%
“…Sen et al also reported that in patients with a soft-tissue defect, acute or gradual compression at the docking site allowed primary or delayed primary closure without any secondary reconstructive procedure. 7 There is less need for soft tissue coverage procedures in patients with bone transport, and this also decreases the need for surgery on other body areas for free tissue transfers. 19 El-rosasy also reported acute limb shortening and appropriate skin incisions to close the defect.…”
Section: Discussionmentioning
confidence: 99%
“…Nonunion may present itself as a problem, though occasionally, following intramedullary fixation of the tibial fractures (Zelle et al, 2004;Patil and Montgomery, 2006;Sen et al, 2006). Too much or too little motion at the fracture site, excessive space between fracture fragments, inadequate fixation, infection, soft tissue interposition, inadequate blood supply, and many other factors can lead to nonunion (Shuler 1996;Rosen 1998;Audige et al, 2005;Drosos et al, 2006).…”
Section: Discussionmentioning
confidence: 99%